CRISPR/Cas9-based QF2 knock-in at the tyrosine hydroxylase (th) locus reveals novel th-expressing neuron populations in the zebrafish mid- and hindbrain - Altbürger, Christian; Holzhauser, Jens; Driever, Wolfgang (Frontiers in Neuroanatomy, 2023)
Catecholaminergic neuron clusters are among the most conserved neuromodulatory systems in vertebrates, yet some clusters show significant evolutionary dynamics. Because of their disease relevance, special attention has been paid to mammalian midbrain dopaminergic systems, which have important functions in motor control, reward, motivation, and cognitive function. In contrast, midbrain dopaminergic neurons in teleosts were thought to be lost secondarily. Here, we generated a CRISPR/Cas9-based knock-in transgene at the th locus, which allows the expression of the Q-system transcription factor QF2 linked to the Tyrosine hydroxylase open reading frame by an E2A peptide. The QF2 knock-in allele still expresses Tyrosine hydroxylase in catecholaminergic neurons. Coexpression analysis of QF2 driven expression of QUAS fluorescent reporter transgenes and of th mRNA and Th protein revealed that essentially all reporter expressing cells also express Th/th. We also observed a small group of previously unidentified cells expressing the reporter gene in the midbrain and a larger group close to the midbrain–hindbrain boundary. However, we detected no expression of the catecholaminergic markers ddc, slc6a3, or dbh in these neurons, suggesting that they are not actively transmitting catecholamines. The identified neurons in the midbrain are located in a GABAergic territory. A coexpression analysis with anatomical markers revealed that Th-expressing neurons in the midbrain are located in the tegmentum and those close to the midbrain–hindbrain boundary are located in the hindbrain. Our data suggest that zebrafish may still have some evolutionary remnants of midbrain dopaminergic neurons.